The Growing Spine Management of Spinal Disorders in Young Children - Akbarnia, Behrooz A.; Yazici, Muharrem; Thompson, George H. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
Spinal disorders in very young children may be caused by a variety of conditions. The treatment of such conditions is often challenging due to the age of the patient and the progressive nature of the deformity. There also may be associated problems such as congenital anomalies, respiratory insufficiency, and neurological problems. Depending on the etiology of the deformity, these children are often cared for by multiple specialists including pediatricians, pediatric orthopaedists or orthopaedic spine surgeons, neurologists, pediatric surgeons, pediatric neurosurgeons, oncologists, and/or pulmonologists. Health professionals in all of the mentioned disciplines are involved in the management of these patients, which is why compiling a comprehensive textbook that is not limited to orthopedic specialists is essential. This textbook will effectively help to standardize the care of these patients. Furthermore, other professionals such as nurses, physical therapists and healthcare professionals in training are usually not familiar with these conditions and are in need of a reference book to consult when caring for children with spinal deformities.